2006
DOI: 10.1016/j.yhbeh.2005.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid inhibition of female sexual behavior by gonadotropin-inhibitory hormone (GnIH)

Abstract: TitleRapid inhibition of female sexual behavior by gonadotropin-inhibitory hormone (GnIH). Abstract Gonadotropin-releasing hormone (GnRH) is largely responsible for the initiation of sexual behaviors; one form of GnRH activates a physiological cascade causing gonadal growth and gonadal steroid feedback to the brain, and another form is thought to act as a neurotransmitter to enhance sexual receptivity. In contrast to GnRH, gonadotropin-inhibitory hormone (GnIH) inhibits gonadotropin release. The distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 28 publications
6
119
0
Order By: Relevance
“…These data suggest that RFRP-3 may be an important central player in maintaining homeostasis within the reproductive system. Recent reports have suggested that rat RFRP-3 is functionally similar to the described GnIH in birds (Bentley, Jensen, Kaur, Wacker, Tsutsui, and Wingfield, 2006;Kriegsfeld et al, 2006). Although structurally related to GnIH, the mammalian homolog, RFRP-3, appears to have multiple physiologic and behavioral functions in the adult male rat.…”
Section: Discussionmentioning
confidence: 97%
“…These data suggest that RFRP-3 may be an important central player in maintaining homeostasis within the reproductive system. Recent reports have suggested that rat RFRP-3 is functionally similar to the described GnIH in birds (Bentley, Jensen, Kaur, Wacker, Tsutsui, and Wingfield, 2006;Kriegsfeld et al, 2006). Although structurally related to GnIH, the mammalian homolog, RFRP-3, appears to have multiple physiologic and behavioral functions in the adult male rat.…”
Section: Discussionmentioning
confidence: 97%
“…The GnRH system plays a key role in vertebrate reproduction, and GnIH decreases gonadotropin release and synthesis via the GnRH system in birds (Tsutsui et al, 2000;Ciccone et al, 2004;Osugi et al, 2004;Bentley et al, 2006;Ubuka et al, 2006). GnRH and GnIH are secreted by the hypothalamus and partially regulate the gonadotropins FSH and LH, as well as PRL (Tsutsui et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Another key neurohormone in the HPG axis is gonadotropin-inhibitory hormone (GnIH), which is a neuropeptide expressed in quail (Tsutsui et al, 2000), chicken (Ikemoto and Park, 2005), sparrow (Osugi et al, 2004), starling (Ubuka et al, 2008), zebra finch (Tobari et al, 2010), and goose. GnIH decreases gonadotropin release and synthesis via the GnRH system in birds (Tsutsui et al, 2000;Ciccone et al, 2004;Osugi et al, 2004;Bentley et al, 2006;Ubuka et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The synchronous and diurnal variations of LPXRFa and its receptor genes indicate that the action of LPXRFa on the diencephalon is highly dependent on time, and thereby LPXRFa might be involved in the control of the cyclic reproductive activity of grass puffer. One of possible target sites of LPXRFa action in the diencephalon may be GnRH neurons as reported in other vertebrates [34,37,45]. RFRP-3 Rat Inhibition of GnRH-elicited GTH release [62] RFRP-3 Ovin Inhibition of GnRH-elicited GTH release [58] Bullfrog fGRP Bullfrog Stimulation of GH release [17] fGRP-RP-2 Bullfrog Stimulation of GH/PRL release [19] Goldfish LPXRFa-1 Sockeye salmon Stimulation of GTH and GH release [54] Goldfish LPXRFa-2 Sockeye salmon Stimulation of GTH and GH release [54] Goldfish LPXRFa-3 Sockeye salmon Stimulation of GTH and GH release [54] Zebrafish LPXRFa-3 Goldfish Inhibition of LH release [43] Goldfish LPXRFa-1 Grass puffer Stimulation of GTH release [51] Photoperiodic regulation of LPXRFa gene has been reported in some vertebrates.…”
Section: Regulatory Mechanism Of Lpxrfa Biosynthesismentioning
confidence: 87%
“…QRFP and 26RFa [27,28]. Among these groups of the RFamide peptide family, the LPXRFa group regulates the release of various pituitary hormones; however, the precise effects of LPXRFa vary distinctly among animal classes [9,10,12,13,19,[29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%